Tectonic evolution of the central part of the East Anatolian Fault Zone, Eastern Turkey - Akgun, Elif; Inceoz, Murat (Tubitak Scientific & Technological Research Council Turkey, 2021)
The Eastern Anatolian Fault Zone (EAFZ), having a prominent place in the tectonic evolution of the Eastern Mediterranean, is a structural element of tectonic indentor due to the convergence between the African-Arabian plates and the Eurasian Plate. This study investigates the central part of EAFZ between Doganyol (Malatya) and celikhan (Adiyaman). The geometry of the fault and the morphotectonic structures were determined by the field studies. Moreover, fault-slip data are measured according to the fault planes along the deformation zone for paleostress analysis. The paleostress analysis revealed three deformation phases that developed from the Late Eocene to the present due to the convergence between the Arabian Plate and the Anatolian Block. The first deformation phase is characterized by NW-SE compressional stress between Late Eocene and Late Oligocene periods. The second deformation phase is related to N-S compressional stress from the Middle Miocene to Pliocene. The most recent deformation phase shows the strike-slip faulting under the NNE-SSW compressional stress from the Late Pliocene to the present. The EAFZ developed during the last phase of these deformation stages. In addition, elongated ridges parallel to the fault, sinistral offsets of drainage networks, linear valleys, and fault terraces observed along the segment show that the study area exhibits active tectonic morphology of the EAFZ. The distribution of seismic activity that occurred during and after the recent mainshock (24 January 2020, Sivrice-Doganyol earthquake) is compatible with the geometry of the segment and confirms strongly the active tectonics of the segment.
Keywords: East Anatolian Fault Zone; paleostress analysis; deformation phase; Sivrice-Doganyol earthquake